Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt G=2^2017+2^2016+...+2+1
=>2G=2^2018+2^2017+...+2^2+2
=>G=2^2018-1
=>H=2^2018-2^2018+1=1
=>2018^H=2018
M = 2^2018 - (2^2017 + 2^2016 + ...+ 2^1+2^0)
Đặt N = 2^2017+2^2016+...+2^1+2^0
=> 2N=2^2018 +2^2017+...+2^2+2^1
=> 2N-N = 2^2018 - 2^0
N = 2^2018 - 1
Thay N vào M có
M = 2^2018 - (2^2018-1)
M = 2^2018 - 2^2018 + 1
M = 1
\(\left(x+1\right)^6+\left(y-1\right)^4=-z^2\)
\(\Rightarrow\left(x+1\right)^6+\left(y-1\right)^4+z^2=0\)
Ta có: \(\hept{\begin{cases}\left(x+1\right)^6\ge0\\\left(y-1\right)^4\ge0\\z^2\ge0\end{cases}}\Rightarrow\left(x+1\right)^6+\left(y-1\right)^4+z^2\ge0\)
Mà \(\left(x+1\right)^6+\left(y-1\right)^4+z^2=0\)
\(\Rightarrow\hept{\begin{cases}\left(x+1\right)^6=0\\\left(y-1\right)^4=0\\z^2=0\end{cases}}\Rightarrow\hept{\begin{cases}x=-1\\y=1\\z=0\end{cases}}\)
Thay x = -1, y = 1, z = 0 vào P
\(\Rightarrow P=2018.\left(-1\right)^{2016}.1^{2017}-\left(0-1\right)^{2018}\)
\(=2018-1=2017\)
Vậy...
Ta có \(A=1+2+2^2+2^3+...+2^{2017}\)
Suy ra\(2.A=2+2^2+2^3+2^4+....+2^{2018}\)
Khi đó \(2A-A=2+2^2+2^3+2^4+....+2^{2018}-\left(1+2+2^2+2^3+....+2^{2017}\right)\)
Hay \(A=2^{2018}-1\)
Ta thấy \(A=2^{2018}-1\); \(B=2^{2018}-1\)nên \(A=B\)
Vậy \(A=B\)
1) (x + 2016)2016 + |y - 2017|2017 = 0
\(\Leftrightarrow\hept{\begin{cases}\left(x+2016\right)^{2016}=0\\\left|y-2017\right|^{2017}=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x+2016=0\\y-2017=0\end{cases}}\Leftrightarrow\hept{\begin{cases}x=-2016\\y=2017\end{cases}}\)
\(A=2^{2017}+2^{2016}+...+2+1\)
\(\Leftrightarrow2A=2^{2018}+2^{2017}+...+2^2+2\)
=>\(A=2^{2018}-1\)
\(D=2^{2018}-2^{2018}+1=1\)